Graphene hydrogel based on waste lithium battery negative electrode graphite as well as preparation method and application of graphene hydrogel
By pretreating the graphite anode material from waste lithium batteries and preparing graphene hydrogels, the problem of structural instability of graphite anode material after charging and discharging was solved, and graphene hydrogels with high efficiency recycling and high adsorption performance were achieved, which are suitable for wastewater treatment.
Patent Information
- Application Number
- CN202510971236.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-10-31
AI Technical Summary
In existing technologies, the interlayer spacing of graphite anodes from waste lithium batteries increases and surface defects and cracks appear after charge-discharge cycles, which increases the processing difficulty. Furthermore, changes in its chemical properties affect its adsorption performance, making recycling difficult.
By pretreating the graphite anode material from waste lithium batteries, including calcination and ball milling, graphene powder is prepared and then mixed with a hydrogel pretreatment solution. Tetramethylethylenediamine is added and allowed to stand to form a graphene hydrogel. This fully utilizes the graphene's porous structure and high specific surface area to achieve efficient adsorption of pollutants.
It has achieved efficient recycling and reuse of graphite anodes from waste lithium batteries. The graphene hydrogel exhibits significant adsorption performance in water, which can efficiently intercept and degrade pollutants, and the process is pollution-free and low-cost.
Smart Images

Figure CN120860938A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of waste lithium battery recycling technology, specifically relating to a graphene hydrogel based on graphite anode material from waste lithium batteries, its preparation method, and its application. Background Technology
[0002] The positive electrode of spent lithium-ion batteries contains abundant precious metals such as nickel (Ni), cobalt (Co), and manganese (Mn), accounting for approximately 31% of the battery's total weight, while the negative electrode contains as much as 22% graphite. Failure to properly recycle these resources will not only result in enormous waste but also cause serious environmental pollution. Therefore, the recycling of spent lithium-ion batteries is of paramount importance for alleviating resource shortages and promoting the sustainable development of the new energy industry.
[0003] Currently, research on retired lithium batteries both domestically and internationally mainly focuses on the recycling of precious metals from the cathode. For example, the Chinese invention patent "A Method for Recycling Cathode Powder from Waste Lithium-ion Batteries" (He Zhenjiang et al., patent number CN116706307A) proposes a technical solution: using waste lithium-ion battery cathode powder as the cathode and an inert electrode as the negative electrode, charging it in an electrolyte solution. After charging, a precursor material with a multilayer structure and a lithium-rich solution can be obtained through solid-liquid separation.
[0004] However, the recycling value of graphite anodes from spent lithium-ion batteries is often overlooked. In fact, after thousands of charge-discharge cycles, graphite anodes still maintain a complete layered structure, with increased interlayer spacing compared to the initial graphite, and surface defects and cracks may appear. These properties allow graphite anodes to be effectively utilized in the preparation of novel materials with superior performance.
[0005] However, after charge-discharge cycles, the interlayer spacing of graphite anodes increases, and surface defects and cracks appear. While this may increase its specific surface area and adsorption active sites, it also leads to structural inhomogeneity, increasing the difficulty of subsequent processing and modification. For example, maintaining the stability of the graphite layered structure and controlling its defect degree during the preparation of adsorbent materials to avoid affecting adsorption performance is an urgent problem to be solved. Furthermore, surface defects and cracks may cause changes in the chemical properties of graphite, such as introducing more active functional groups or altering the surface charge distribution. These changes may have unpredictable effects on the selectivity and adsorption capacity of the target substances. Therefore, how to effectively utilize waste lithium-ion battery anode graphite to prepare high-performance adsorbent materials still requires further research. Summary of the Invention
[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0007] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0008] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing graphene hydrogel based on graphite from waste lithium battery negative electrode.
[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution: including,
[0010] Pretreated waste lithium battery negative electrode graphite is calcined and ball-milled to obtain graphene powder;
[0011] Graphene powder was added to pure water and ultrasonically treated to obtain a graphene dispersion.
[0012] Acrylamide, methylenebisacrylamide and potassium persulfate were added to pure water and ultrasonically treated to obtain a hydrogel pretreatment solution;
[0013] After the graphene dispersion and the hydrogel pretreatment solution are mixed and ultrasonically homogenized, tetramethylethylenediamine is added, and the mixture is allowed to stand to obtain the graphene hydrogel.
[0014] As a preferred embodiment of the preparation method of graphene hydrogel based on waste lithium battery negative electrode graphite of the present invention, the pretreatment of the waste lithium battery negative electrode graphite includes boiling water soaking and peeling, washing, drying and sieving.
[0015] In a preferred embodiment of the method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite according to the present invention, the waste lithium battery negative electrode graphite is calcined in a nitrogen atmosphere with a nitrogen flow rate of 20-50 m / s. 3 / h, roasting temperature is 450~500℃, roasting time is 1~2h.
[0016] As a preferred embodiment of the preparation method of graphene hydrogel based on waste lithium battery negative electrode graphite of the present invention, wherein: the grinding ball in the ball milling treatment of the waste lithium battery negative electrode graphite is an iron ball with a diameter ranging from 4 to 8 mm.
[0017] As a preferred embodiment of the method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite according to the present invention, the ball milling ball-to-material ratio is 12-16:1, the ball milling time is 24-64 hours, and the ball milling frequency is 24-32Hz.
[0018] In a preferred embodiment of the method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite according to the present invention, the concentration of the graphene dispersion is 2-10 mg / ml.
[0019] In a preferred embodiment of the method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in this invention, the mass ratio of acrylamide, methylenebisacrylamide, potassium persulfate, and water is 1:0.01-0.02:0.05-0.1:5-8.
[0020] In a preferred embodiment of the method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in this invention, the volume ratio of the mixture of tetramethylethylenediamine, graphene dispersion and hydrogel pretreatment solution is 1:3 to 7.5.
[0021] Another objective of this invention is to provide a method for preparing graphene hydrogels based on graphite from waste lithium-ion battery negative electrodes.
[0022] Another objective of this invention is to provide an application of graphene hydrogel based on waste lithium battery negative electrode graphite in the adsorption treatment of methylene blue.
[0023] Beneficial effects of this invention:
[0024] This invention provides a graphene hydrogel based on waste lithium-ion battery negative electrode graphite, its preparation method, and its application. This method utilizes the synergistic effect of multiple reagents to tightly bind ball-milled graphene with the hydrogel, successfully converting waste graphite from waste lithium-ion batteries into a graphene hydrogel. This process not only achieves efficient recycling and reuse of waste graphite from waste lithium-ion battery negative electrodes but also fully leverages the material's porous structure, high specific surface area, and high photocatalytic performance, enabling it to effectively adsorb, intercept, and degrade pollutants in water. This recycling method features low processing costs, high utilization rate of waste graphite materials, and no pollution, demonstrating significant economic value. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0026] Figure 1 This is a schematic diagram of the preparation process of graphene hydrogel based on waste lithium battery negative electrode graphite in an embodiment of the present invention.
[0027] Figure 2This is a picture of the finished graphene hydrogel prepared in Example 1 of the present invention.
[0028] Figure 3 This is a comparison image of the graphene hydrogel prepared in Example 1 of the present invention before and after adsorption of methylene blue.
[0029] Figure 4 The graph shows the adsorption kinetics curves of methylene blue in water for the graphene hydrogels prepared in Examples 1-4 and Comparative Example 1 of this invention. Detailed Implementation
[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0031] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0033] Unless otherwise specified, all raw materials used in this invention are commercially available in the field.
[0034] The raw material used in this invention, waste lithium battery negative electrodes, comes from Shanghai Maikun International Logistics.
[0035] Example 1
[0036] Reference Figure 1 This embodiment provides a method for producing graphene hydrogels based on graphite from waste lithium battery negative electrodes, specifically as follows:
[0037] 1) Soak the waste lithium battery negative electrode sheet in boiling water for half an hour to remove the waste graphite on it. After filtration, wash and filter the removed waste graphite with pure water. Repeat the washing and filtration process 3 times. Place it in a drying oven to dry. Sieve the dried waste graphite to obtain pre-treated coarse waste graphite powder.
[0038] 2) The pretreated crude waste graphite powder is placed in a calcination furnace and kept at 500°C for 1.5 hours in a nitrogen atmosphere, during which the nitrogen flow rate is maintained at 30 m3 / h. After the heat preservation is completed, the finished waste graphite powder can be obtained.
[0039] 3) The finished waste graphite powder is put into a high-energy ball mill, the ball milling frequency is set to 28Hz, the ball milling time is 48 hours, the diameter of the grinding balls is 5mm, and the ball-to-material ratio is 15:1. After ball milling, graphene powder is obtained.
[0040] 4) Add 25mg of graphene powder to 5ml of pure water and sonicate until the mixture is homogeneous to obtain a graphene dispersion with a concentration of 5mg / ml.
[0041] 1.5g acrylamide, 0.025g methylenebisacrylamide and 0.08g potassium persulfate were ultrasonically mixed with 13.8g water to obtain a hydrogel pretreatment solution;
[0042] Mix 5 ml of graphene dispersion with 10 ml of hydrogel pretreatment solution and sonicate for 15 min. Add 3 ml of tetramethylethylenediamine and let stand for 5 min to obtain the graphene hydrogel based on waste lithium battery negative electrode graphite in this embodiment.
[0043] Example 2
[0044] The difference between this embodiment and Embodiment 1 is that the concentration of the graphene dispersion in step 4) of Embodiment 1 is adjusted to 2 mg / ml, the mass of graphene powder and pure water is mixed in a ratio of 2:1, and the remaining steps are the same as in Embodiment 1, so as to obtain the graphene hydrogel of this embodiment.
[0045] Example 3
[0046] The difference between this embodiment and Embodiment 1 is that the concentration of the graphene dispersion in step 4) of Embodiment 1 is adjusted to 10 mg / ml, the mass of graphene powder and pure water is mixed in a ratio of 10:1, and the remaining steps are the same as in Embodiment 1, so as to obtain the graphene hydrogel of this embodiment.
[0047] Example 4
[0048] The difference between this embodiment and Example 1 is that the volume ratio of the mixture of tetramethylethylenediamine and graphene dispersion + hydrogel pretreatment solution in step 4) of Example 1 is adjusted to 1:3 (wherein, tetramethylethylenediamine is 5 ml, graphene dispersion is 5 ml, and hydrogel pretreatment solution is 10 ml). The remaining steps are the same as in Example 1, and the graphene hydrogel of this embodiment is obtained.
[0049] Comparative Example 1
[0050] The difference between this comparative example and Example 1 is that the calcination and ball milling steps of the pretreated crude waste graphite powder are omitted, and graphite molten gel is prepared directly using pretreated graphite as raw material. Specifically:
[0051] 1) Soak the waste lithium battery negative electrode sheet in boiling water for half an hour to remove the waste graphite on it. After filtration, wash and filter the removed waste graphite with pure water. Repeat the washing and filtration process 3 times. Place it in a drying oven to dry. Sieve the dried waste graphite to obtain pre-treated coarse waste graphite powder.
[0052] 2) Add 25mg of crude waste graphite powder to 5ml of pure water and sonicate until the mixture is homogeneous to obtain a crude waste graphite dispersion with a concentration of 5mg / ml.
[0053] 1.5g acrylamide, 0.025g methylenebisacrylamide and 0.08g potassium persulfate were ultrasonically mixed with 13.8g water to obtain a hydrogel pretreatment solution;
[0054] Mix 5 ml of crude waste graphite dispersion with 10 ml of hydrogel pretreatment solution and sonicate for 15 min. Add 3 ml of tetramethylethylenediamine and let stand for 5 min to obtain the graphene hydrogel of this comparative example.
[0055] Application testing
[0056] The hydrogels prepared in Examples 1 to 4 and Comparative Example 1 of this invention were applied to adsorb methylene blue from water, specifically:
[0057] A 400 mg / L methylene blue solution was prepared, and 25 ml of this solution was accurately transferred to a test tube. Then, 1 g of the graphene hydrogel sample prepared in the example / comparative example was placed into the solution and allowed to stand for 8 hours in a dark environment to evaluate its adsorption efficiency. The experimental results are as follows: Figure 3 , 4 As shown.
[0058] Figure 2 This is a picture of the finished graphene hydrogel prepared in Example 1 of the present invention. Figure 3 These are comparison images of the graphene hydrogel prepared in Example 1 of this invention before and after adsorption of methylene blue. Figure 4 The graph shows the adsorption kinetics curves of methylene blue in water for the graphene hydrogels prepared in Examples 1-4 and Comparative Example 1 of this invention.
[0059] As shown in the attached figures, the method of Example 1 of this application can efficiently convert waste graphite from waste lithium batteries into graphene hydrogels, transforming graphene powder, which is originally difficult to collect from sewage, into a three-dimensional graphene structure with high adsorption performance and easy recycling. The hydrogels prepared in Examples 1 to 4 showed good adsorption performance for methylene blue, with the highest adsorption capacity reaching 328.64 mg / g within 1 hour and the total adsorption capacity reaching as high as 648.25 mg / g within 3 hours. This fully demonstrates that the graphene hydrogels synthesized by this method have significant potential in practical applications.
[0060] Example 5
[0061] This embodiment is used to investigate the effect of ball milling time on the properties of the prepared hydrogel. Specifically, the ball milling time in step 3) of Example 1 was adjusted to 24, 36, 48, 60 and 72 hours respectively. The remaining steps were the same as in Example 1. Composite self-cleaning membranes with different ball milling times were obtained in this embodiment, and their adsorption capacity for methylene blue was tested. The results are shown in Table 1.
[0062] Table 1
[0063] Ball milling time / h Adsorption capacity per hour / mg / g 3-hour adsorption capacity / mg / g 24 291.22 369.57 36 325.53 415.53 48 328.64 648.25 60 224.78 453.44 72 286.34 480.75
[0064] As can be seen from Table 1, different ball milling times have a significant impact on the properties of the prepared hydrogels. The 48-hour ball milling time used in this method is beneficial for producing graphene structures with higher porosity because the ball milling energy can be better transferred to the graphite at this time, which is conducive to the formation of porous structures.
[0065] Example 6
[0066] This embodiment is used to investigate the effect of the ball-to-material ratio during ball milling on the performance of the prepared hydrogel. Specifically, the ball-to-material ratio in step 3) of Example 1 was adjusted to 12:1, 13:1, 14:1, 15:1, and 15:1, respectively. The remaining steps were the same as in Example 1. Graphene hydrogels with different ball-to-material ratios were obtained, and their adsorption capacity for methylene blue was tested. The results are shown in Table 2.
[0067] Table 2
[0068]
[0069]
[0070] As shown in Table 2, different ball-to-material ratios significantly affect the adsorption performance of graphene hydrogels, with a 15:1 ratio being particularly crucial. At this ratio, the energy utilization and conduction efficiency of the collisions between the balls and graphite within the mill jar are high, which helps to form a porous graphene structure and thus improves its adsorption performance.
[0071] Example 7
[0072] This embodiment is used to investigate the effect of the ball diameter during ball milling on the performance of the prepared hydrogel. Specifically, the ball diameter in step 3) of Example 1 was adjusted to 4, 5, 6, 7 and 8 mm respectively. The remaining steps were the same as in Example 1. Graphene hydrogels with different ball milling diameters were obtained in this embodiment, and their adsorption capacity for methylene blue was tested. The results are shown in Table 3.
[0073] Table 3
[0074] Small ball diameter / mm Adsorption capacity per hour / mg / g 3-hour adsorption capacity / mg / g 4 132.65 265.37 5 328.64 648.25 6 243.56 344.23 7 224.12 313.76 8 176.41 287.69
[0075] Table 3 shows that the diameter of the milling balls significantly affects the performance of the graphene hydrogel, with 5mm diameter balls performing exceptionally well. This size of ball generates moderate shear and impact forces during milling, which is beneficial for forming a porous graphene structure. If the ball diameter is too large, the excessive impact force will damage the graphene structure; while if the ball diameter is too small, insufficient energy and excessive shear force will result, which is detrimental to the formation of porous structures and high specific surface area graphene.
[0076] Example 8
[0077] This embodiment investigates the effect of tetramethylethylenediamine dosage on the performance of prepared hydrogels. Specifically, the dosage of tetramethylethylenediamine in step 7) of Example 1 was adjusted to 1, 2, 3, 4, and 5 ml. At this time, the volume ratio of tetramethylethylenediamine to the mixed solution (graphene dispersion and hydrogel pretreatment solution) was 1:15, 1:7.5, 1:5, 1:3.75, and 1:3, respectively. The remaining steps were the same as in Example 1. Graphene hydrogels with different tetramethylethylenediamine dosages were obtained in this embodiment. The adsorption capacity for methylene blue and the hardness after swelling equilibrium were tested. The results are shown in Table 4.
[0078] Table 4
[0079] Tetramethylethylenediamine dosage / ml 3-hour adsorption capacity / mg / g Compressive strength after swelling equilibrium 1 645.78 0.2 kPa 2 643.32 1.1 kPa 3 648.25 3.2 kPa 4 633.17 4.8 kPa 5 631.39 5.4 kPa
[0080] Table 4 shows that the amount of tetramethylethylenediamine (TMD) has little effect on the adsorption of methylene blue by the graphene hydrogel, with the adsorption amount remaining around 640 mg / g after 3 hours. The maximum adsorption amount (648.25 mg / g) is achieved when the amount of TMD is 3 ml. However, the amount of TMD significantly affects the compressive strength of the graphene hydrogel after swelling equilibrium. As the amount of TMD increases, the compressive strength of the graphene hydrogel after swelling equilibrium also increases. A certain strength after swelling equilibrium facilitates separation from water. Experiments show that when the compressive strength of the hydrogel is greater than 2.8 kPa, it will not break when handled with tweezers. Therefore, when the amount of TMD is 3 ml, the graphene hydrogel still has good strength after swelling equilibrium, facilitating separation from water. However, excessive TMD reduces the adsorption effect of the graphene hydrogel on methylene blue.
[0081] In summary, this invention relates to a method for preparing graphene hydrogel using waste lithium-ion battery anode materials and its applications. First, the waste lithium-ion battery anode graphite undergoes a series of pretreatments, including soaking and peeling, washing, drying, sieving, calcination for impurity removal, and ball milling, to obtain graphene powder. Next, the graphene powder is prepared into a dispersion and mixed with a hydrogel pretreatment solution. Tetramethylethylenediamine is then added and allowed to stand, ultimately yielding the graphene hydrogel. This method, through the synergistic effect of various chemical reagents, achieves a tight bond between graphene and hydrogel, fully utilizing the advantages of both's porosity and high specific surface area, enabling efficient adsorption of pollutants in water and facilitating recycling and reuse. This method not only has low processing costs but also high utilization rates of waste graphite materials, and the entire process is pollution-free, demonstrating broad application prospects.
[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing graphene hydrogel based on graphite from waste lithium battery negative electrodes, characterized in that: include, Pretreated waste lithium battery negative electrode graphite is calcined and ball-milled to obtain graphene powder; Graphene powder was added to pure water and ultrasonically treated to obtain a graphene dispersion. Acrylamide, methylenebisacrylamide and potassium persulfate were added to pure water and ultrasonically treated to obtain a hydrogel pretreatment solution; After the graphene dispersion and the hydrogel pretreatment solution are mixed and ultrasonically homogenized, tetramethylethylenediamine is added, and the mixture is allowed to stand to obtain the graphene hydrogel.
2. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 1, characterized in that: The pretreatment of the waste lithium battery negative electrode graphite includes boiling water soaking and peeling, washing, drying and sieving.
3. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 2, characterized in that: The waste lithium battery negative electrode graphite is calcined in a nitrogen atmosphere, wherein the nitrogen flow rate is 20-50 m / s. 3 / h, roasting temperature is 450~500℃, roasting time is 1~2h.
4. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 1, characterized in that: The grinding balls used in the ball milling process of the waste lithium battery negative electrode graphite are iron balls with a diameter ranging from 4 to 8 mm.
5. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 4, characterized in that: The ball-to-material ratio of the ball mill is 12–16:1, the ball milling time is 24–64 hours, and the ball milling frequency is 24–32 Hz.
6. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 1, characterized in that: The concentration of the graphene dispersion is 2–10 mg / ml.
7. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 1, characterized in that: The mass ratio of acrylamide, methylenebisacrylamide, potassium persulfate, and water is 1:0.01-0.02:0.05-0.1:5-8.
8. The method for preparing graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 6, characterized in that: The volume ratio of the mixture of tetramethylethylenediamine, graphene dispersion, and hydrogel pretreatment solution is 1:3 to 7.
5.
9. Graphene hydrogel based on waste lithium battery negative electrode graphite prepared by any of the preparation methods described in claims 1 to 8.
10. The application of the graphene hydrogel based on waste lithium battery negative electrode graphite as described in claim 9 in the adsorption treatment of methylene blue.
Citation Information
Patent Citations
Method for recovering positive electrode powder of waste lithium ion battery
CN116706307A